Migration route, stopping sites, and non-breeding destinations of adult Black-tailed Godwits breeding in southwest Fryslân, The Netherlands - Verhoeven, Mo A.; Loonstra, A. H. Jelle; McBride, Alice D.; Both, Christiaan; Senner, Nathan R.; Piersma, Theunis (Journal of Ornithology, 2021)
In this paper, we extend our understanding of the migration of Black-tailed Godwits (Limosa limosa limosa) by describing: (1) the orientation and geographic locations of individual migratory routes and (2) the spatial distribution of godwits across seasons and years. We accomplish this using satellite-tracking data from 36 adult godwits breeding in the 200-ha Haanmeer polder in The Netherlands, from 2015 to 2018. During both southward and northward migration, godwits used a narrow migratory corridor along which most individuals made stops within a network of sites, especially the Bay of Biscay, France and Doñana, Spain. Most sites were used consistently by the same individuals across years. However, sites in Morocco were used during northward migration by 75% of individuals, but not revisited by the same individual across years. After southward migration, a small proportion (15%) of godwits spent the entire non-breeding period north of the Sahara, but most (85%) crossed the Sahara and spent at least part of the non-breeding season among seven coastal sites in West Africa and one site in the Inner Niger Delta. Although site-use patterns varied among individuals, individuals showed high site fidelity and were consistent in the number of sites they used from year to year. The considerable differences in the spatial distribution of individuals that breed within a kilometre of one another raise questions about the causes and consequences of individual migratory differences. We discuss that full annual cycle tracking of juveniles from birth to adulthood is needed to understand the source of these individual differences. Our results on the spatial distribution of godwits throughout their annual cycle lay an important foundation of information that can be used to help conserve this declining species.